MRI of the Intrinsic Muscles of the Hand - Andreisek, Gustav; Kislinger, Benedikt; Dessouky, Riham; Chhabra, Avneesh (Seminars in Musculoskeletal Radiology, 2017)
This review article reviews muscle function and anatomy, describes normal magnetic resonance (MR) imaging anatomy, and shows a spectrum of abnormal imaging findings. It covers the lumbrical, interosseous, and thenar and hypothenar muscles. The described spectrum of abnormalities includes anatomical variants, exercise-induced MR signal changes, denervation syndromes, and myositis, as well as tumors. Advanced imaging techniques are discussed at the end to provide a look at future hand muscle imaging.
Keywords: magnetic resonance imaging; hand; muscles